Obraz kobiet w przysłowiach polskich i koreańskich - Choi, Yoon Kyo (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2014)
During my research I found many similarities related to women’s image retained in proverbs of both nations, but also some differences. There are common characteristics conditioned by the similarities of women’s position and role in the Korean and Polish history. For example, women were, in both cultures, the inferior sex, illogical beings, the objects subordinated culturally and legally to men, the creatures prone to betrayal, chatty, clever, sly, mischievous, vain, extravagant and quarrelsome. Despite the apparent misogyny, the proverbs—both Korean and Polish—acknowledge in various aspects, the existence of women, who are better and nobler than men, also signal significant influence of women upon men. In addition, the authors of proverbs appreciate such positive qualities of women as feminine goodness, gentleness, economy, being a good companion of life for a man, etc. In contrast, clear differences between the image of women in the Korean and Polish proverbs are related to the fact that in the Polish proverbs the dominant image of women is the image of a person who is clever, often associated with the devil, which in the Korean proverbs does not occur at all. Another significant difference between the Korean and the Polish proverbs consists in the presentation of a tragic fate of women who, in the former Korea depended absolutely on men, believing in many superstitions associated with women.